Protecting embers to light the qulliit of Inuit learning in Nunavut communities - Tompkins, Joanne; McAuley, Alexander; Walton, Fiona (Études/Inuit/Studies, 2009)
On July 1, 2009 at a special ceremony in Iqaluit, 21 Inuit women graduated from Nunavut’s first graduate degree program, a Master of Education in Leadership and Learning offered by the University of Prince Edward Island in partnership with Nunavut Department of Education, St. Francis Xavier University, and Nunavut Arctic College. The authors of this article, Northwest Territories/Nunavut educators between 1982 and 1999, and university-based professors and researchers who have since been involved in the planning and delivery of the Nunavut M.Ed., trace the roots of the program to decolonising research in educational practices in the Baffin region between 1980 and 1999. They then outline the design and implementation of the program with particular emphasis on its challenges and the approaches necessary for its success.